Surgical Pulmonary Embolectomy: Four Cases Report - Uysal, Ayhan; Burma, Oktay; Özgüler, Murat (Fırat University, 2012)
Acute massive or submassive pulmonary embolism (PE) requires prompt diagnosis and aggressive treatment. Mortality rates can rise up to 70% within the first hour of presentation and are strongly correlated with the degree of right ventricular (RV) dysfunction, cardiac arrest, and consequential congestive heart failure. Pulmonary embolectomy was performed on 4 cases that diagnosed as pulmonary embolism (PE) at Department of Cardio-vascular Surgery, School of Medicine of Fırat University. Three of the cases were female, one was male and the avarage age was 51 (32-67). Deep vein thrombosis was present in all patients. The cause of deep vein thrombosis was trauma in two patient, oral contraseptives use in one and gyneco-logic operation in one patient. The preoperative diagnosis was established by echocardiography and computed tomography. In four patients with MPE, urgent pulmony embolectomy were performed by median sternotomy, using extracorporeal circulation (ECC). Mortality was observed in one case (%25). This patient had taken to operating room with resuscitation because of cardiac arrest. We conclude that, pulmonary embolectomy using ECC in early period of life-threatening MPE may be a life saver procedure

Akut masif ya da submasif pulmoner emboli hızlı tanı ve tedaviyi gerektirir.Tanının ilk saatinden itibaren mortalite oranları %70'lere kadar yükselebilmektedir. Bu durum sağ ventrikül disfonksiyonunun derecesi, kardiyak arrest ve konjestif kalp yetmezliğinin derecesi ile korelasyon göstermektedir. Pulmoner emboli tanısı almış 4 vakaya, Fırat Üniversitesi Tıp Fakültesi Kalp Damar Cerrahisi Anabilimdalı'nda pulmoner embolektomi operasyonu uygulandı. Hastaları 3'ü bayan ,1'i erkek olup ortalama yaş 51(32-67) idi. Derin ven trombozu tüm hastalarda mevcut olup etiyolojide 2 hastada travma, 1 hastada oral kontraseptif kullanımı ve 1 hastada da major jinekolojik operasyon olduğu saptandı. Masif Pulmoner Emboli tanısı ekokardiyografi ve bilgisayarlı tomografik anjiografi ile konuldu. Hemodinamik olarak instabilitesi olan tüm hastalara ekstrakorporeal dolaşım desteği altında medyan sternotomi yoluyla pulmoner embolektomi uygulandı. Mortalite 1 hastada gözlendi. Bu hasta da kardiyak arrest nedeniyle resüsitasyon eşliğinde operasyona alınan hasta idi. Hayatı tehdit eden MPE' lilerde ekstrakorporeal dolaşım (EKD) şartlarında erken dönemde yapılacak pulmoner embolektominin hayat kurtarıcı olacağını düşünmekteyiz.
Cerrahi Pulmoner Embolektomi: Dört Olgunun Sunumu